A Pilot Investigation of Cognitive Behavioural Therapy for Clinical Perfectionism in Obsessive Compulsive Disorder - Sadri, S.; Anderson, Rebecca; McEvoy, P.; Kane, Robert; Egan, Sarah (Cambridge University Press, 2017)
Copyright © British Association for Behavioural and Cognitive Psychotherapies 2017Background: Perfectionism is strongly associated with obsessive compulsive disorder (OCD). Cognitive behavioural therapy for perfectionism (CBT-P) has been found to result in reductions in a range of symptoms in individuals with anxiety disorders, depression and eating disorders. Aim: To pilot-test the efficacy of group CBT for perfectionism in participants with OCD and elevated perfectionism. Method: Participants were randomized to receive immediate 8-week group CBT-P (n = 4) or an 8-week waitlist followed by CBT-P (n = 7). Results: Reliable reductions and a large effect size indicated that CBT-P was associated with improvements in perfectionism and OCD severity at post-test. However, these changes were not clinically significant and drop-out was high, resulting in a small final sample. Conclusions: CBT-P may be effective in reducing perfectionism and disorder-specific OCD symptoms. However, the high drop-out rate and lack of clinically significant findings suggest that further research needs to be conducted to determine the efficacy of CBT for perfectionism in OCD.